Faktor-Faktor Yang Mempengaruhi Perkembangan Aset Pada Ksu Bmt Radja Syariah Payakumbuh - Tezi Asmadia; Indah Novebriana (Saqifah: Jurnal Hukum Ekonomi Syariah, 2021)
The purpose of this study was to analyze the factors that influence the development of total assets at KSU BMT Radja Syariah Payakumbuh. Data collection techniques used in using interview and documentation techniques. The data analysis technique that the author uses in this study is in the form of data reduction, data presentation, and drawing conclusions. The primary data sources in this study were the directors and employees of KSU BMT Radja Syariah Payakumbuh and the secondary data sources in this study were customer brochures, financial reports, and other documents related to the problems the authors examined. The results obtained are that the factors that influence the development of assets at KSU BMT Radja Syariah Payakumbuh are the existence of Third Party Funds (DPK) in the form of savings and deposits, then distribution of financing by KSU BMT Radja Syariah to customers, and the number of offices owned by KSU BMT Radja Syariah so that the coverage is wider. Although the development of assets at KSU BMT Radja Syariah is quite good, in developing its assets KSU BMT Radja Syariah has obstacles, namely limited Human Resources, the economic condition of the community during the corona pandemic, and other classic problems.